Exploring the mobile learning needs amongst performing arts students. Issue 2 (29th April 2020) - Fan, Ken Yiu Kwan; Lo, Patrick; Ho, Kevin K.W.; So, Stuart; Chiu, Dickson K.W.; Ko, Eddie H.T.
Abstract : Purpose: This paper aims to study the information needs and online information-seeking behaviors on mobile platforms of performing arts students at a college level. Design/methodology/approach: Survey instruments were used to collect data from performing arts students at the Hong Kong Academy of Performing Arts (HKAPA), a metropolitan's major performing arts tertiary institution. Data collected were analyzed through descriptive statistics and other statistical methods, and the music-related students were compared with the production-related students. Findings: The result reveals that performing arts students all owned their mobile devices and often used mobile apps for non-academic purposes, but they did not often use mobile library services or read online academic contents with their mobile devices. The participants considered inadequate signal coverage, slow loading time, difficulty in reading on a mobile device and the lack of specialized mobile apps as more significant barriers affecting their usage. There are some significant differences between the music-related and production-related student groups in that music-related students watched lectures on the library websites and used electronic music scores more often than the production-related students. Practical implications: This study contributes to the input for enhancements and policies to future mobile services and facilities of performing art libraries. Originality/value: There have been scant studies on the mobile learning needs of performing arts students, especially in Asia.